DAGMARITA SHHREZAENSIS N. SP. GLOBIVALVULINID FORAMINIFER, (WUCHIAPINGIAN, LATE PERMIAN, CENTRAL IRAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
In the course of an investigation on the major mass extintion event near the P/T boundary, in the vicinity of Shahreza (South Isfahan) in Iran, a stratigraphically significant new species of foraminifera (Dagmarita shahreaensis n. sp.) has been discovered in the Wuchiapingian/Dzhulfian (Late Permian) of central Iran (Hambast Formation). This new species is described and emplaced in the phylogeny of the globivalvulinid foraminifera, which evolved rapidly during the Middle/Late Permian.